Exploring Different Synthesis Parameters for the Preparation of Metal-Nitrogen-Carbon Type Oxygen Reduction Catalysts. Issue 5 (11th February 2020) - Teppor, Patrick; Jäger, Rutha; Härk, Eneli; Sepp, Silver; Kook, Mati; Volobujeva, Olga; Paiste, Päärn; Kochovski, Zdravko; Tallo, Indrek; Lust, Enn
Abstract : The influence of various synthesis conditions of a metal-nitrogen-carbon (M-N/C) catalyst material on oxygen reduction reaction (ORR) kinetics is discussed. Seven M-N/C catalysts based on cobalt are obtained by changing various synthesis conditions, such as the mixing environment, pyrolysis gas, and post-treatment. The ORR activity and stability measurements are performed using the classical three-electrode configuration in a 0.1 M HClO4 solution. The most active and stable ORR catalyst proves to be the material obtained by mixing a cobalt salt, 2, 2'-bipyridine, and a high surface area silicon carbide derived carbon together in water and pyrolyzing the mixture in argon. In a fuel cell test, however, a maximum power density value of 135 mW cm −2 is achieved with the catalyst mixed together in a planetary ball-mill at a low catalyst loading of 1.0 ± 0.1 mg cm −2 and at a test cell temperature of 60 o C despite of the fact that preparing the catalyst via dry ball-milling reduces the surface area of the material roughly 40% more than in the case of using a solution-based method. Consequently, mixing the catalyst precursors together without any additional chemicals in a planetary ball-mill instead of in a solution appears to be the most promising choice.